Cloning and analysis of cathepsin B gene of Radopholus similis - LI Danlei; LI Yu; XIE Hui; XU Chunling; Huang Xin (浙江大学学报. 农业与生命科学版)
The banana burrowing nematode, Radopholus similis, is a migratory endoparasite plant nematode and severely harms many tropical and subtropical crops. It is the most important invasive species to banana worldwide, and is listed as a quarantine pest in many countries. Nematicide have been used as the main approach to control R. similis. However, due to the high toxicity, nematicide has led to many environmental problems. Now, gene targeting has become a new sustainable strategy to control plant nematode. Cathepsin B is a lysosomal cysteine protease, and it occurs in a wide range of parasitic and free-living nematodes. It has been demonstrated that cathepsin B plays a very important role in egg hatching, development, reproduction, invading host, inducing host pathogenesis and immune evasion in parasites. To our knowledge, there are few studies on plant parasitic nematode cathepsin. Until now only one cathepsin B gene from Bursa phelenchus xylophilus (GenBank: GU130153) has been cloned, but the detail gene function is still unclear.The R. similis cathepsin B gene was cloned and analyzed, to provide a scientific basis for the further research on the function of plant-parasitic nematodes cathepsin B, and also for developing new control strategies.A cDNA library of R. similis was constructed by switching mechanism at 5′ end of the RNA transcript (SMART) technique. The full-length cDNA sequence of the cathepsin B gene was obtained by the method of splicing leader (SL), and then sequenced. The homolog sequences of cathepsin B were analyzed to generate a phylogenetic tree. The three-dimensional structure and the function of the cathepsin B protein were also analyzed and forecasted by bioinformatics technology.A mixed stages of R. similis complementary cDNA library was constructed by SMART. Altogether 76 expressed sequence tags (ESTs) were analyzed by Blast in NCBI. Of the 76 ESTs, one 600 bp EST sequence showed high homology to the cathepsin B gene of Caenorhabditis elegans. Based on the 600 bp EST sequence, a 1 257 bp cDNA full-length sequence of the cathepsin B gene from R. similis was cloned by SL, and named as Rs-cb-1 (GenBank accession No: GU360972). A phylogenetic tree was constructed based on the cathepsin B gene sequences of various organisms. The complete Rs-cb-1 ORF is 1 071 bp, and encodes a polypeptide with 356 amino acids (the protein molecular weight is 41.4 ku). The multiple sequence alignment between Rs-cb-1 and the cathepsin B gene of other parasites showed that Rs-cb-1 had the closest genetic relationship with the cathepsin B gene of C. elegans. The function analysis showed that the protein coded by Rs-cb-1 was mainly for cell external secretion protein. The protein was subcellular located in the microbody (peroxisome), the endoplasmic reticulum membrane and the endoplasmic reticulum antrum. A 25 amino acids' transmembrane section was found at the C terminus of the protein. The protein surface charge was polarity distribution. Three-dimensional structure of the protein was drawn by SWISS-MODEL. The structure was consistent with the biological function of cathepsin B gene.Rs-cb-1 was the first record about cathepsin B gene from R. similis. Based on the analysis and forecast, it may have the important biological functions.